Hosting Large Sports Events Sustainably: A Contemporary Administrative and Economic Evaluation - Kamenecka-Usova, Marina; Lejniece, Ilona; Zalcmane, Karina (European Journal of Sustainable Development, 2024)
In the modern era characterized by digitalization and technological advancement, it is especially important to understand whether the country is ready to host large sports events sustainably from contemporary legal, administrative and economic point of view. Therefore, the aim to explore the administrative and economic dimensions of hosting large sports events through the lens of sustainability. This evaluation is crucial for policymakers, event organizers, and stakeholders committed to fostering a balance between economic gains, environmental preservation, and social well-being in the planning and execution of future large-scale sporting events. The methodological foundation of the study is built upon a range of general scientific methods, including the monographic, analytical, historical, and comparative methods, as well as the techniques of induction and deduction. Additionally, the study employs various methods for interpreting legal norms, such as grammatical, historical, teleological, and systemic approaches. Keywords: economic activity and impact assessment, good governance, sports law